Differential Diagnosis of Schistosomiasis: Future Approaches, Limitations and Challenges - Fatemah Enad M Alajmi, (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background: Schistosomiasis, recognized as the second most detrimental parasitic disease in tropical regions, has considerable public health implications in areas where it is endemic. Numerous disease control strategies, especially mass drug administration (MDA) implemented through school-based or community-wide initiatives, have an important impact in decreasing infection transmission rates among high-risk populations. However, one of the primary barriers to successful disease control is the absence of reliable diagnostic tools. It is widely acknowledged that current diagnostic practices for schistosomiasis largely depend on traditional techniques. Despite this, minor disease symptoms, alongside the limited sensitivity and specificity of these conventional diagnostic methods, continue to present significant challenges for healthcare professionals. Consequently, there is a pressing need to develop innovative, practical, and more accurate diagnostic tools and biomarkers to enhance the detection of this infection. Obtaining affordable, user-friendly, and precise diagnostic solutions for schistosomiasis remains a significant hurdle, limiting the scope of initiatives for comprehensive disease control. Along with striving to create novel diagnostic methods, efforts should also focus on refining the existing tools to improve their effectiveness. Objective: This review explores current diagnostic approaches for schistosomiasis, emphasizing their limitations and challenges while suggesting potential future methods. Additionally, it aims to examine the biomedical tools used for identifying and diagnosing biomarkers related to schistosomiasis. Conclusions: The success of efforts to eliminate schistosomiasis is heavily reliant on the precise detection of infections using highly sensitive diagnostic tests, particularly in cases of low-intensity infections. Adequate sanitation infrastructure is lacking, especially in tropical and subtropical regions, highlighting the urgent need for biomedical tools can identify and diagnose new biomarkers for schistosomiasis.